CHARACTERISTICS OF CYBERSOCIALIZATION OF THE DIGITAL GENERATION - Habinskaya, A.A (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2019)
The phenomenon of cyber-socialization of the digital generation drew researchers' attention in the late twentieth followed by another "wave" of information and technological progress. It was established that a dramatic change in the amount of information, ways of its transmission and storage, made it possible to move to a qualitatively new stage of evolution - cyberevolution which generated a new demand for new needs, motivation, goals, attitudes in a person, as well as new forms of interaction and activities directly related to the development of Internet technologies. Nowadays, the Internet is not only a new technology that has no spatial boundaries and time frame. It's a dynamic sector of cyberspace, which is an accelerant for the appearance of new forms of life, new fundamental changes in social structures in the society. At the same time, the Internet is a specific factor in the sociocultural development of the younger generation - personal socialization in cyberspace. Through the description of various opportunities and threats of the world wide web, the author of the article reveals the significant psychological peculiarities and aspects of digital generation mentality: active behavior in cyberspace; creation of artificial reality; preference for gamified communications and computer games; fragmentation and a lack of overall context in consciousness.